Nilai Moral dalam Komik Bacaan Anak Terbitan Book Dash - Muhammad Rafdi Hadyan Auzan (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
This research is entitled Moral Values in Children's Reading Comics published by Book Dash. The aim of this research is to analyze the moral values in children's reading comics published by Book Dash. The method used in this research is a descriptive qualitative method. The approach used in this research uses an objective approach. Based on the results of the research and discussion, it was concluded that the dialogue contained in the children's reading comics published by Book Dash contains moral values found in everyday life. The dialogue in several series published by Book Dash contains several moral values that researchers found in the reading comics, including the relationship between humans and themselves, the relationship between humans and God, the relationship between humans and nature, and the relationship between humans and other humans.